Assessment of wear and technical condition of engines - Dashyvets, Halyna; Дашивець, Галина Іванівна (Запоріжжя : 2023, 2023)
EN: During the operation of the engines, as a result of the wear of the friction pairs, metal elements accumulate in the lubricant. The concentration of wear products in crankcase oil is proportional to the intensity of wear of parts and allows for earlier detection of emergency wear when it is not yet determined by other diagnostic methodаs. The concentration of metal elements in the lubricant, which characterize the technical condition of the engine as a whole and its individual parts, can be determined by spectroscopic analysis. The method allows you to obtain information about the rate of wear of parts, the quality of the filters, the tightness of the cooling system, and the timing of oil replacement. To solve these problems, it is necessary to identify indicator metals and limit values for the content of wear products in the lubricant for the parts of a certain engine.
Keywords: spectral analysis; wear and technical condition of engines; wearing parts; method